Hashimoto’s thyroidits and other causes of hypothyrodisim – systematic review - Jurek, Aleksander; Szumlas, Zuzanna; Mrozek, Łukasz; Klocek, Konrad; Zwolski, Maciej; Puchalski, Krzysztof; Kostecki, Bartosz; Hajduk, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction and objective: The aim of the study is to summarize the knowledge about hypothyroidism, with particular emphasis on Hashimoto's disease, as its most common cause. Review metods: Literature review of PubMed database using key words contained in ‘Medical Subject Headings’ MeSH. State of Knowledge: Hashimoto's disease is the most common form of thyroiditis, as well as main cause of hypothyroidism. It is an autoimmune disease that leads to gradual fibrosis and atrophy of the thyroid gland. It occurs several times more frequently in women than in men. Treatment mainly involves supplementation of thyroid hormones due to the progressive hypothyroidism. Levothyroxine (L-T4) therapy has a long history of clinical use, a defined pharmacological profile, and is considered as safe treatment of hypothyroidism of the thyroid gland. There are also other, less common causes of hypothyroidism, such as postoperative hypothyroidism, de Quervain's disease, post-radioactive iodine treatment status, drug-induced and central hypothyroidism, which are equally important and should not be forgotten during the diagnostic process. Summary: Hypothyroidism can be caused by various factors, the main being Hashimoto’s thyroiditis. Regardless of the etiology, treatment in most cases involves levothyroxine (LT-4) supplementation, which leads to euthyroidism and resolution of symptoms. Surgery may need to be performed in pateitns who meet the surgical criteria and show unresponsiveness to conservative treatment.